HUBUNGAN POWER OTOT TUNGKAI DENGAN LARI JARAK PENDEK 100 METER SISWA KELAS X SMA NEGERI 9 PEKANBARU - Zolika '; Saripin '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem which was observed by the researcher was the lack of physical condition for students to move quickly. And then, the bad result of students in 100-meter sprint was caused by lack of practise in mastering 100-meter sprint which was given by the teacher. The aim of the research was to figure the correlation between the power of the leg muscle and 100-meter sprint out for the tenth grade students of Senior High School 9 Pekanbaru. The design of the research was correlation and the population was 14 people. Total Sampling Technique was used in the research to find the samples. The researcher used Standing Broad Jumps and 100-meter sprint in collecting data. The taken data was analysed by using Product Moment Correlation. Regarding to data analyses, there was a significant correlation between the power of leg muscle and 100-meter sprint for the tenth grade students of Senior High School 9 Pekanbaru which was rtable α (0.05) = 0.0532 and rcount (0.639) > rtab (0.532)Keyword: the power of the leg muscle, 100-meter sprint